Healing properties of papain-based gel on oral ulcers - Martins, Manoela Domingues (2016)
The oral mucous membrane is prone to developing ulcers originating from traumatic or immunological processes. Aim: The aim of the present study was to perform a histological evaluation of the antiinflammatory and healing properties of PapacarieTM applied to oral ulcers. Methods: Fifty adult female albino Wistar rats were randomly separated into two groups: control and PapacarieTM. The animals were anesthetized, placed in prone position and ulcers were induced in the middle dorsum of the tongue through a 3-mm-diameter punch. The control group received no treatment thereafter, while those in the PapacarieTM group received an application of the gel twice a day for 14 days. Five animals from each group were euthanized on days 1, 3, 5, 7 and 14. The tongues were removed, fixed, routinely processed for hematoxylin-eosin staining and analyzed by two blind, calibrated pathologists for the presence or absence of ulcer, inflammatory infiltrate and neutrophils. Data were submitted to statistical analysis by the Fisher’s exact test. Results: On day 1, both groups exhibited ulceration and dense acute inflammatory infiltrate. On day 5, reepithelization and scanty chronic inflammatory infiltrate were observed. On day 14, all animals were healed. There were no statistically significant differences between groups with regard to ulceration (p=0.81), inflammation (p=0.55) or neutrophils (p=0.53). Conclusions: Oral ulcers treated with a papainbased gel exhibited the same inflammatory reaction and healing aspects as those of the nontreated control group.